2022
DOI: 10.1177/02692155221134240
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of aquatic exercise in knee osteoarthritis: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objective To examine the efficacy and safety of aquatic exercise for people with knee osteoarthritis. Data sources PubMed, Web of Science, Embase, CENTRAL, CNKI and WanFang databases were searched from 1966 to September 2022. Review methods Randomized controlled trials evaluating aquatic exercise for people with knee osteoarthritis compared with no exercise and land-based exercise were included. The Grading of Recommendations Assessment, Development and Evaluation system was used to evaluate the certainty of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…In contrast to previous systematic reviews [7,[24][25][26][27][28][29][30][31], this meta-analysis showed that aquatic exercise improved functionality measured with TUG, decreased joint stiffness measured with WOMAC, and relieved knee joint pain measured with VAS. These signi cant changes occurred for 1 to 4 months while the intervention was maintained.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous systematic reviews [7,[24][25][26][27][28][29][30][31], this meta-analysis showed that aquatic exercise improved functionality measured with TUG, decreased joint stiffness measured with WOMAC, and relieved knee joint pain measured with VAS. These signi cant changes occurred for 1 to 4 months while the intervention was maintained.…”
Section: Discussioncontrasting
confidence: 99%
“…Likewise, another review reports that aquatic exercise is bene cial for the reduction of knee OA pain, especially if the water is warmer [28]. Finally, a recent systematic review evaluates the effect of aquatic exercise in patients with knee OA compared to land-based exercise, with the main result that aquatic exercise provides a clinical bene t in the short term that is maintained for 3 months after the intervention [29]. This review is the one that most closely resembles the present study; however, the difference is the fact that we included studies that incorporated an educational program in addition to other exercise modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic exercise is considered a safe alternative for patients who are not suitable for weight‐bearing exercises due to its ability to reduce joint weight‐bearing and potential joint damage. According to current evidence, 48–54 the guideline panel found that aquatic exercise provides pain relief (SMD = −0.52, 95% CI: −0.74 to −0.3), improves functional capacity (SMD = −0.37, 95% CI: −0.7 to −0.04), and enhances the 6‐min walking distance (SMD = 0.44, 95% CI: 0.08 to 0.8). However, the sustained effect of symptom relief from water exercise is shorter, with effectiveness lasting up to 3 months postintervention.…”
Section: Resultsmentioning
confidence: 99%
“…According to current evidence, [48][49][50][51][52][53][54] −1.12 to 0.15) in patients with knee osteoarthritis, according to metaanalyses. 82,83 It has also demonstrated some benefits for joint mobility and walking performance.…”
Section: B Evidence Summarymentioning
confidence: 99%